Caspase-1-Dependent and -Independent Cell Death Pathways in Burkholderia pseudomallei Infection of Macrophages - Antje Bast (2018)
The cytosolic pathogen Burkholderia pseudomallei and causative agent of melioidosis has been shown to regulate IL-1β and IL-18 production through NOD-like receptor NLRP3 and pyroptosis via NLRC4. Downstream signalling pathways of those receptors and other cell death mechanisms induced during B. pseudomallei infection have not been addressed so far in detail. Furthermore, the role of B. pseudomallei factors in inflammasome activation is still ill defined. In the present study we show that caspase-1 processing and pyroptosis is exclusively dependent on NLRC4, but not on NLRP3 in the early phase of macrophage infection, whereas at later time points caspase-1 activation and cell death is NLRC4- independent. In the early phase we identified an activation pathway involving caspases-9, -7 and PARP downstream of NLRC4 and caspase-1. Analyses of caspase-1/11-deficient infected macrophages revealed a strong induction of apoptosis, which is dependent on activation of apoptotic initiator and effector caspases. The early activation pathway of caspase-1 in macrophages was markedly reduced or completely abolished after infection with a B. pseudomallei flagellin FliC or a T3SS3 BsaU mutant. Studies using cells transfected with the wild-type and mutated T3SS3 effector protein BopE indicated also a role of this protein in caspase-1 processing. A T3SS3 inner rod protein BsaK mutant failed to activate caspase-1, revealed higher intracellular counts, reduced cell death and IL-1β secretion during early but not during late macrophage infection compared to the wild-type. Intranasal infection of BALB/c mice with the BsaK mutant displayed a strongly decreased mortality, lower bacterial loads in organs, and reduced levels of IL-1β, myeloperoxidase and neutrophils in bronchoalveolar lavage fluid. In conclusion, our results indicate a major role for a functional T3SS3 in early NLRC4-mediated caspase-1 activation and pyroptosis and a contribution of late caspase-1-dependent and -independent cell death mechanisms in the pathogenesis of B. pseudomallei infection. © 2014 Bast et al.